Proses Transaksi Jual Beli Pinang Karungan di Desa Tungkal 1 Kecamatan Tungkal Ilir - Anisah Anisah (Lembaga Yasin AlSys, 2026)
The practice of buying and selling plantation commodities at the community level still presents problems related to honesty, fairness in weighing, and price transparency. Studies that specifically discuss sack-based areca nut transactions from the perspective of Islamic economics remain limited, particularly in the context of the community of Tungkal I Village, Tungkal Ilir Subdistrict. This study aims to analyze the process of sack-based areca nut buying and selling and to examine its conformity with the principles of Islamic economics. This study employed a qualitative approach with a descriptive design. The research informants consisted of areca nut sellers, toke, and religious figures selected through the snowball sampling technique. Data were collected through field observations, interviews, and documentation, and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that sack-based areca nut transactions are conducted using manual platform scales and hanging scales. Before the transaction takes place, sellers and toke generally understand the mechanisms of weighing and price determination. However, this practice still contains several problems, such as sellers mixing weight-increasing materials, including stones, soil, and twigs, into sacks of areca nuts, as well as the rounding of weights by toke when the weight of the areca nuts does not reach a certain threshold. These findings indicate that the practice of sack-based areca nut buying and selling is not yet fully consistent with the principles of fairness, honesty, mutual consent, and accuracy in measurement in Islamic economics. This study contributes to enriching the study of fiqh muamalah concerning sack-based local commodity transactions and emphasizes the importance of a more transparent, fair, and mutually beneficial buying and selling system for both sellers and buyers.